Dependence of spontaneous electrical activity and basal prolactin release on nonselective cation channels in pituitary lactotrophs - Kučka, Marek; Kretschmannová, Karla; Stojilković, Stanko S; Zemková, Hana; Tomić, M (Physiological research, 2012)
All secretory anterior pituitary cells fire action potentials spontaneously and exhibit a high resting cation conductance, but the channels involved in the background permeability have not been identified. In cultured lactotrophs and immortalized GH(3) cells, replacement of extracellular Na(+) with large organic cations, but not blockade of voltage-gated Na(+) influx, led to an instantaneous hyperpolarization of cell membranes that was associated with a cessation of spontaneous firing. When cells were clamped at -50 mV, which was close to the resting membrane potential in these cells, replacement of bath Na(+) with organic cations resulted in an outward-like current, reflecting an inhibition of the inward holding membrane current and indicating loss of a background-depolarizing conductance. Quantitative RT-PCR analysis revealed the high expression of mRNA transcripts for TRPC1 and much lower expression of TRPC6 in both lactotrophs and GH(3) cells. Very low expression of TRPC3, TRPC4, and TRPC5 mRNA transcripts were also present in pituitary but not GH(3) cells. 2-APB and SKF-96365, relatively selective blockers of TRPC channels, inhibited electrical activity, Ca(2+) influx and prolactin release in a concentration-dependent manner. Gd(3+), a common Ca(2+) channel blocker, and flufenamic acid, an inhibitor of non-selective cation channels, also inhibited electrical activity, Ca(2+) influx and prolactin release. These results indicate that nonselective cation channels, presumably belonging to the TRPC family, contribute to the background depolarizing conductance and firing of action potentials with consequent contribution to Ca(2+) influx and hormone release in lactotrophs and GH(3) cells.
Keywords: Lactotrophs; Animals; Rats; Sodium; Female; ženské pohlaví; Action Potentials; prolaktin; časové faktory; TRPC Cation Channels; modulátory membránového transportu; Time Factors; kationtové kanály TRPC; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; vápník; kultivované buňky; Rats, Sprague-Dawley; RNA, Messenger; Cells, Cultured; iontové kanály; Ion Channels; Calcium; Reverse Transcriptase Polymerase Chain Reaction; potkani Sprague-Dawley; sodík; laktotropní buňky; Patch-Clamp Techniques; krysa rodu Rattus; Membrane Transport Modulators; zvířata; metoda terčíkového zámku; Prolactin; kvantitativní polymerázová řetězová reakce; akční potenciály; Real-Time Polymerase Chain Reaction